Alien Nation: Chinese Migration in the Americas from the Coolie Era through World War II - Lim, Julian (Labour / Le Travail, 2017)
This article reviews the book, "Alien Nation: Chinese Migration in the Americas from the Coolie Era through World War II," by Elliott Young.